A small gathering of bones - Powell, Patricia 1966- (Caribbean writers series, 1994)
Dale's passionate relationship with Nevin is foundering. Hope and despair, jealousy and yearning battle within him. He must confront the antagonism of family, church and society to his homosexuality. A mysterious illness is threatening the gay community of late 1970s Jamaica. When Dale's friends succumb to it, his own isolation increases and he is pushed towards desperate action.